The Application of Microfluidic Technologies in Aptamer Selection - Liu, Yang; Wang, Nijia; Chan, Chiu-Wing; Lu, Aiping; Yu, Yuanyuan; Zhang, Ge; Ren, Kangning (Frontiers in Cell and Developmental Biology, 2021)
Aptamers are sequences of single-strand oligonucleotides (DNA or RNA) with potential binding capability to specific target molecules, which are increasingly used as agents for analysis, diagnosis, and medical treatment. Aptamers are generated by a selection method named systematic evolution of ligands by exponential enrichment (SELEX). Numerous SELEX methods have been developed for aptamer selections. However, the conventional SELEX methods still suffer from high labor intensity, low operation efficiency, and low success rate. Thus, the applications of aptamer with desired properties are limited. With their advantages of low cost, high speed, and upgraded extent of automation, microfluidic technologies have become promising tools for rapid and high throughput aptamer selection. This paper reviews current progresses of such microfluidic systems for aptamer selection. Comparisons of selection performances with discussions on principles, structure, operations, as well as advantages and limitations of various microfluidic-based aptamer selection methods are provided.